Practical resolution tips for trigonometric ratios with remarkable angles (Research, Society and Development, 2020)
This paper aims to demonstrate and analyze a proposal for the teaching of trigonometric reasons in the right triangle, emphasizing the remarkable angles, through less pragmatic and complex teacher's orientations, in order to generate faster and more practical thinking. of the student when seeking the solution of the problem situation. In this regard, a bibliographic research of the trigonometric approach of the rectangle triangle of textbooks with renowned authors in Brazil, such as Mathematics Science and Application by Iezzi et al., (2007), Mathematics Contexts & Applications by Dante (2013), Complete Mathematics, was conducted. Giovanni e Bonjorno (2005) and Connections to Barroso's mathematics (2010), aiming to find methodological support that corroborates our research. Therefore, the methodological procedures were divided into two strands: in the first moment the explanations of the proposed subject on the direction of the methodology of teaching Polya Problem Solving in two distinct classes were performed, in a second moment two evaluations were applied, one with the method. present in some textbooks analyzed and another according to the proposal of our work, in a strand more focused on the style used in the courses, which use practical tips and easy memorization, known prosaically as "Bizu". The analysis of the students' evaluations presented the following results: 63% of correct answers in the classical approach and 88% of correct answers in the methodology of our proposal, which led us to make several reflections inherent to teaching and learning and the ways to pass the mathematical contents. , more specifically trigonometric ratios.